Towards in vivo intradermal surface enhanced Raman scattering (SERS) measurements: silver coated microneedle based SERS probe - Yuen, Clement (2013)
We propose a microneedle coated with silver (Ag) to detect analytes at low concentrations positioned at a depth of more than 700 μm below the surface of a skin phantom with absorbers and scatterers for mimicking the intradermal surface-enhanced Raman scattering (SERS) measurements. The Ag layer in the Ag-coated microneedle-based probe is found to be the key to the effective detection of analytes buried inside the aforesaid phantom. Glucose concentrations ranging from 5 to 150 mM inside phantoms can be estimated with a root mean square error (RMSE) of 3.3 mM. This work shows the potential of using microneedles for simple in vivo intradermal SERS measurements of analytes with clinical relevance.